2016
DOI: 10.1016/j.jvs.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and factors influencing prognosis in patients with vascular pythiosis

Abstract: Achieving adequate disease-free surgical margins-especially the arterial margin-at amputation or débridement is the most important prognostic factor in patients with vascular pythiosis. Early detection combined with a multidisciplinary approach to treatment, including surgery, antifungal agents, and immunotherapy, allows the best possible outcome to be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 14 publications
3
46
1
2
Order By: Relevance
“…In our study, definitive surgery was performed in 49 of 50 (98%) patients. This is likely the reason why the mortality rate in our study decreased to 10% from 36.4% to 44.4% in the previous studies (13,14,29). As expected, patients who survived had a significant shorter mean duration from the onset of disease to their first medical encounters as well as a shorter mean waiting time for their definitive surgeries.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, definitive surgery was performed in 49 of 50 (98%) patients. This is likely the reason why the mortality rate in our study decreased to 10% from 36.4% to 44.4% in the previous studies (13,14,29). As expected, patients who survived had a significant shorter mean duration from the onset of disease to their first medical encounters as well as a shorter mean waiting time for their definitive surgeries.…”
Section: Discussionsupporting
confidence: 56%
“…Previous data support claims that PiV proteins have the ability to modulate the Th2 response in cases of pythiosis to a Th1 response after successful immunotherapy [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 23]. Using the mouse Leishmania model, we demonstrated that the Th2 response in place during experimental L. major mice experimental infection of BALB/c mice, switched to a polarized Th1 response.…”
Section: Discussionsupporting
confidence: 79%
“…However, few immunotherapeutic proteins of microbial origin are presently being considered for immunotherapy; one of them is PiV, while the rest represent antigenic epitopes harvested from cancer patients [33, 37]. So far, PiV antigenic preparation has shown minimal or no side effects in experimental animals (1,2,10,13, this study), and in cured humans and animals with pythiosis [3, 4, 5, 6, 7, 8, 9, 10, 11, 13, 14, 23]. Based on these results, we anticipate further interest in PiV immunomodulatory capabilities applied to other infectious and non-infectious processes that otherwise involve a non-curative Th2 response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, definitive surgery was performed in 49/50 (98%) patients. This is likely the reason why the mortality rate in our study decreased to 10% from 36.4%-44.4% in the previous studies (2, 3, 17). As expected, patients who survived had a significant shorter mean duration from the onset of disease to their first medical encounters as well as a shorter mean waiting time for their definitive surgeries.…”
Section: Discussioncontrasting
confidence: 57%